2001
DOI: 10.1007/978-94-017-3674-9_74
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Methods for Developing Heterotic Groups in Wheat (Triticum aestivum)

Abstract: Wheat lines could be clustered into different groups based on their agronomic traits, or general combining ability (GCA) of agronomic traits, or molecular markers. Hybrids from parents in different groups were generally superior to most hybrids from parents in the same group. But there were apparent differences in heterosis for different heterotic groups based on different methods. This study showed that the average heterosis of heterotic groups based on RAPD markers is much higher than that of heterotic group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Here, previous studies concluded that: (i) there were no correlations between heterosis or hybrid performance and genetic distance for grain yield (Barbosa-Neto et al 1996;Corbellini et al 2002;Dreisigacker et al 2005;Liu et al 1999;Martin et al 1995 Solomon et al 2007), (ii) there were significant but too low correlations for practical use (Corbellini et al 2002;El-Maghraby et al 2005), and (iii) there were significant correlations but only for a limited number of traits excluding grain yield (Corbellini et al 2002;Martin et al 1995;Perenzin et al 1998;Solomon et al 2007;Krystkowiak et al 2009). Nonetheless, while genetic distance per se does not appear to be an adequate predictor for hybrid performance in wheat, there is still the general trend of increased heterosis accompanying increased genetic diversity of parental lines which is in line with quantitative genetic theory (Brears and Bingham 1989;Morgan et al 1989;Falconer and Mackay 1996;Liu et al 1999Liu et al , 2001El-Maghraby et al 2005;Fu et al 2014). In contrast to maize, the absence of a clear association between genetic distance and heterosis might also be explained by the generally low level of heterosis in wheat.…”
Section: The Importance Of Genetic Distance For the Establishment Of mentioning
confidence: 86%
“…Here, previous studies concluded that: (i) there were no correlations between heterosis or hybrid performance and genetic distance for grain yield (Barbosa-Neto et al 1996;Corbellini et al 2002;Dreisigacker et al 2005;Liu et al 1999;Martin et al 1995 Solomon et al 2007), (ii) there were significant but too low correlations for practical use (Corbellini et al 2002;El-Maghraby et al 2005), and (iii) there were significant correlations but only for a limited number of traits excluding grain yield (Corbellini et al 2002;Martin et al 1995;Perenzin et al 1998;Solomon et al 2007;Krystkowiak et al 2009). Nonetheless, while genetic distance per se does not appear to be an adequate predictor for hybrid performance in wheat, there is still the general trend of increased heterosis accompanying increased genetic diversity of parental lines which is in line with quantitative genetic theory (Brears and Bingham 1989;Morgan et al 1989;Falconer and Mackay 1996;Liu et al 1999Liu et al , 2001El-Maghraby et al 2005;Fu et al 2014). In contrast to maize, the absence of a clear association between genetic distance and heterosis might also be explained by the generally low level of heterosis in wheat.…”
Section: The Importance Of Genetic Distance For the Establishment Of mentioning
confidence: 86%